Evaluation of Patients with Parkinson’s Disease in Intensive Care Units: A Cohort Study - Álvaro Réa-Neto; Bruna C. Dal Vesco; Rafaella S. Bernardelli; Aline M. Kametani; Mirella C. Oliveira; Hélio A. G. Teive (Parkinson's Disease)
Background. Parkinson’s disease affects approximately 1% of the worldwide population older than 60 years. This number is estimated to double by 2030, increasing the global burden of the disease. Patients with Parkinson’s disease are hospitalized 1.5 times more frequently and for longer periods than those without the disease, increasing health-related costs. Objective. To compare the characteristics and outcome of patients with and without Parkinson’s disease admitted to intensive care units (ICUs). Methods. Historical cohort study of ICU admissions in a Brazilian city over 18 years. All patients with Parkinson’s disease identified were matched for age, sex, year, and place of hospitalization with patients without the disease randomly selected from the same database. Results. The study included 231 patients with Parkinson’s disease (PD group) and 462 controls without the disease (NPD group). Compared with patients in the NPD group, those in the PD group were more frequently admitted with lower level of consciousness and increased APACHE II severity score but required less frequently vasoactive drugs. In total, 42.4% of the patients in the PD group were admitted to the ICUs due to sepsis or trauma. Although these patients had longer hospital stay, the mortality rates were comparable between groups. Parkinson’s disease was not associated with mortality, even when controlled for associated factors of disease severity. Conclusion. Although patients with Parkinson’s disease were admitted with higher severity scores and remained in the ICU for a longer time, their mortality rate was not higher than that in patients without the disease.